CHANCE (τύχη), FATE (εἱμαρμένη), ‘WHAT DEPENDS ON US’ (τὸ ἐφ' ἡμῖν) AND PROVIDENCE (πρόνοια) IN PLUTARCH'S QUAESTIONES CONVIVALES (Revista Kriterion, 2021)
One of the many philosophical issues discussed throughout Plutarch's Quaestiones convivales (QC) has to do with the origin and inner structure of the universe, i.e., cosmological discussions. It would be impossible to discuss in detail every passage of the treatise that deals with cosmological issues. Therefore, I chose to limit my analysis to the concepts of chance (τύχη), fate (εἱμαρμένη), ‘what depends on us’ (τὸ ἐφ' ἡμῖν), and providence (πρόνοια). My purpose is to explain these concepts in the QC and to extract from them a cosmological doctrine.